2016
DOI: 10.16965/ijar.2016.135
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Size of Yolk Sac by Ultrasonography and Its Correlation With Pregnancy Outcome

Abstract: The yolk sac is the first extra embryonic structure that becomes sonographically visible within the gestational sac and acts as the primary route of exchange between the human embryo and the mother before the placental circulation is established. The yolk sac is a round structure that is made up of an anechoic center bordered by a regular well-defined echogenic rim. It is usually 2-5 mm in diameter. The yolk sac appears at 6 weeks, thereafter increases in size, attains its maximum diameter at 10 weeks and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
3
6
0
Order By: Relevance
“…This was approximately like finding of Srivastava et al which were 11.2%, 10% and 11.4% respectively. 13 Thus, these studies support that abnormal diameter of YS is strongly associated with miscarriage.…”
Section: Discussionsupporting
confidence: 64%
“…This was approximately like finding of Srivastava et al which were 11.2%, 10% and 11.4% respectively. 13 Thus, these studies support that abnormal diameter of YS is strongly associated with miscarriage.…”
Section: Discussionsupporting
confidence: 64%
“…4 So in present study, the mean YSD was more than these other two studies and the largest YSD was smaller in present study than that of study by Srivastav et al, in India. 5 In this study, mean YSD was progressively increasing with advancing gestational age from 6 weeks to 10 weeks 6 days. Cepni et al, demonstrated the steady increase in YSD from 5 to 11 weeks of gestation in normal pregnancies after which it disappears by 12 weeks.…”
Section: Discussionsupporting
confidence: 46%
“…In the study by Srivastav et al, in India, the mean YSD was noted as 3.7±1.8 mm and the diameter of the smallest yolk sac was 1.25 mm and that of the largest was 8.96 mm. 5 In this study, mean YSD was 4.32±1.01 mm. In the study conducted by Tan S et al in Turkey, the mean YSD was 3.2±0.7 mm.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In 2016, Ashoush et al, a large yolk sac was most commonly detected (in 36.8%) with isolated congenital anomalies (representing 63.6% of all cases with too-large yolk sac) [1] . In 2016, Srivastava et al, also reported that an enlarged yolk sac was responsible for 77.78% of the abortions [14] . In this study, an enlarged yolk sac has been noted in seven pregnancies (7.6%) of all cases.…”
Section: Discussionmentioning
confidence: 99%